2020
DOI: 10.22598/mt/2020.32.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Value and Attitude to Catalogs and Store Flyer Ads Among Croatian Consumers – SEM Approach

Abstract: Purpose -This research study aims to determine the infl uence of the factors of informativeness, entertainment, irritation, and credibility on the perception of the value of advertisements and the attitude to advertising through catalogs and store fl yers among Croatian consumers.Design/methodology/approach -In the research, testing a theoretical model of value perception, 354 correct answers were collected via email, Facebook groups, and Internet forums. Hypotheses were tested using structural equation modeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Based on a survey and experimental data collected from respondents in seven countries in regard to ads for orange juice and personal computers, Erdem et al (2006) found that the more information an ad contains, the more willing viewers are to learn about the product. Dobrinic et al (2020) reported that the informativeness of a video ad has an immediate, positive impact on perception by Generation Z users, who form the youngest consumer group.…”
Section: Social Science Studiesmentioning
confidence: 99%
“…Based on a survey and experimental data collected from respondents in seven countries in regard to ads for orange juice and personal computers, Erdem et al (2006) found that the more information an ad contains, the more willing viewers are to learn about the product. Dobrinic et al (2020) reported that the informativeness of a video ad has an immediate, positive impact on perception by Generation Z users, who form the youngest consumer group.…”
Section: Social Science Studiesmentioning
confidence: 99%